Structural Equation Model of Factors Affecting Thai Tourist Post-purchase Behavioral Intentions toward Than Sadet-Ko Pha-Ngan National Park Suratthani Province - Jankingthong, Wiwat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The purpose of this study was to test a structural equation model of factors affecting tourist post-purchase behavioral intentions toward Than Sadet-Ko Pha-Ngan National park. The sample of the study was 400 Thai tourists who visited Than Sadet-Ko Pha-Ngan National park by using accidental sampling. Research hypothesis included five major factors causing tourist post-purchase behavioral intentions with latent variables: corporate social responsibility, destination image, perceived value, tourist satisfaction and tourist complaints. Data were collected by requesting the sample group to answer questionnaires. Lisrel 8.8 Program was employed to test the specified structural equation model. The results revealed that the model was consistent with empirical data at a good level. Meanwhile, perceived value, tourist satisfaction and tourist complaints directly affect tourist post-purchase behavioral intentions, whereas the indirect factors affecting tourist post-purchase behavioral intentions include corporate social responsibility, destination image, perceived value and tourist satisfaction.